Ground Zero - Gratz, Alan, 1972- (New York : Scholastic Press, 2021)
Brandon is visiting his dad on the 107th floor of the World Trade Center on September 11, 2001 when the attack comes; Reshmina is a girl in Afghanistan who has grown up in the aftermath of that attack but dreams of peace, becoming a teacher and escaping her village and the narrow role that the Taliban believes is appropriate for women--both are struggling to survive, both changed forever by the events of 9/11.
Keywords: World Trade Center (New York, N.Y. : 1970-2001) -- Juvenile fiction; World Trade Center (New York, N.Y. : 1970-2001) -- Fiction; September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Afghan War, 2001- -- Juvenile fiction; Teenage boys -- Juvenile fiction -- New York (State); Teenage girls -- Juvenile fiction -- Afghanistan; Survival -- Juvenile fiction; September 11 Terrorist Attacks, 2001 -- Fiction; Afghan War, 2001- -- Fiction; Survival -- Fiction; New York (N.Y.) -- Juvenile fiction -- History -- 21st century; Afghanistan -- Juvenile fiction -- History -- 21st century; New York (N.Y.) -- Fiction; Afghanistan -- Fiction; Historical fiction